THE QUALITY OF BOVINE COLOSTRUM AND THE TRANSFERENCE OF IMMUNITY TO NEWBORN CALVES IN LAGES, SC, BRAZIL - Vaz, Adil K; Furtado, Adroaldo Cervi; Marca, André; Paterno, Marcos Roberto (Revista de Ciências Agroveterinárias, 2004)
Colostrum samples were taken at the first milking from 74 cows in four farms. Serum samples were taken from their calves in the first 72 hours after birth. The levels of immunoglobulins in the colostrum and in the sera were analyzed by the Zinc Turbidity Test. In the colostrum a colostrometer (Schering-Plough Animal Health, United Kingdom) was also used to evaluate the immunoglobulin content. The results were statistically analyzed using InStat software (GraphPad Inc, USA). Immunoglobulin concentration in colostrum ranged from 2719.8 mg/100 mL to 8850.2 mg/100 mL (SD= ±1325.7), and in the sera of the calves from 281.94 mg/ml to 1163.4 mg/100 mL (SD=±238.25). There was no correlation among Ig concentration in the colostrum and serum (p=0.2123). The concentration varied widely among individual dam/calf pairs. Considering the limit of normality as one Standard Deviation below average, 18.92% of the calves had failure of passive transfer. A statistically significant (p=0.0156) difference was observed in the Ig concentration in the serum of calves from two farms, but not in the colostrum of the cows of these farms. There was also a difference (p=0.0121) between Ig concentration in the serum of calves born in winter (576.26 ± 225.28 mg/100 mL ) and in summer (776.4 ± 226,98 mg/100 mL ). This difference did not occur in colostrum. According to the colostrometer scale, colostrum samples were classified as good when they had a density between 1045 and 1090 (79.7% of the samples), regular when the density was between 1035 and 1045 (14.9% of the samples) and poor with densities below 1035 (5.4% of the samples).